Compton valance super f.a.r.t. versus the master of time - Brown, Matt; Finlay, Lizzie (Usborne Pub Ltd; UK, 2015)
Fresh from saving the universe, Compton and Bryan are whisked off to the future to become trainee Time Crime Agents. But when a notorious criminal mastermind escapes from a maximum security prison and kidnaps Bryan, Compton must race against time to save his best friend - and the world - from evil...using only a slimy sandwich!